Mental Health In The Workplace: Overcoming Stigma And Increasing Support - Mokhamad Nurhadi; Yessy Dessy Arna; Erika Erika; Mutmainnah Mutmainnah (PT. Anagata Sembagi Education, 2024)
The first stage of labor often takes a long time and causes discomfort for the mother, so methods are needed to accelerate it. This study aims to evaluate the effectiveness of microcontroller-based nipple stimulation in accelerating the labor process by stimulating the release of the hormone oxytocin which increases uterine contractions and accelerates cervical opening. Microcontroller technology is used to ensure the stimulation is done automatically and measured according to the mother's physiological needs. This study involved two groups, namely the group that received stimulation and the control group that did not receive stimulation. There are shortcomings in studies examining the effectiveness of interventions implemented at the organisational level in reducing stigma and improving mental health support. A variety of strategies can be used to address stigma, including proper education, awareness campaigns, and training for managers and employees on the importance of mental health. The development of inclusive policies and the provision of easy and non-discriminatory access to mental health services are essential. Consistent managerial support also plays a key role in creating a supportive work environment. Creating a positive and inclusive organizational culture will help companies improve employee mental health and well-being, while also increasing workforce productivity and retention. Reducing stigma and increasing support can create a healthier work environment, which ultimately supports individual development and the long-term success of the company.